2018
DOI: 10.1002/aqc.2874
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal acoustic occurrence of blue, fin, and North Atlantic right whales in the New York Bight

Abstract: 1. The New York Bight is an extremely busy maritime region, with extensive shipping traffic and commercial fishing activity. It is part of the migratory ranges of a number of cetacean species, and includes threats from ship strikes, noise exposure, and line entanglements. Previous cetacean surveys of the Bight offer limited information on cetacean occurrence and distribution in the region, having been restricted to visual sightings with limited temporal coverage. A passiveacoustic monitoring survey was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 53 publications
(71 reference statements)
3
21
0
Order By: Relevance
“…Fin whales were present nearly year-round from Virginia (mid-Atlantic; region 8) to eastern Greenland (region 2). These findings correspond with regional studies where fin whales were detected on 99%-100% of recording days in Massachusetts Bay (region 5) and the New York Bight (region 7; Morano et al, 2012;Muirhead et al, 2018). Moreover, these data reflect previous findings of year-round fin whale presence, and support suggestions that, as in other baleen whales, not all fin whales migrate.…”
Section: Fin Whalessupporting
confidence: 90%
See 2 more Smart Citations
“…Fin whales were present nearly year-round from Virginia (mid-Atlantic; region 8) to eastern Greenland (region 2). These findings correspond with regional studies where fin whales were detected on 99%-100% of recording days in Massachusetts Bay (region 5) and the New York Bight (region 7; Morano et al, 2012;Muirhead et al, 2018). Moreover, these data reflect previous findings of year-round fin whale presence, and support suggestions that, as in other baleen whales, not all fin whales migrate.…”
Section: Fin Whalessupporting
confidence: 90%
“…showed that the regions south of New England (region 7) and east of Greenland (region 2) were also important areas for humpback whales, similar to NARWs (Davis et al, 2017;Mellinger et al, 2011;Muirhead et al, 2018).…”
Section: Humpback Whalesmentioning
confidence: 99%
See 1 more Smart Citation
“…Passive acoustic monitoring (PAM) is an ecosystem-based approach to assess long-term changes in community abundance, richness, and diversity primarily based on the aural identification of species [18,101,102]. This methodology is very popular in bioacoustic studies to monitor the abundance, distribution, and reproductive cycles of focus species (e.g., dolphins [103], koalas [104], whales [105], raptors [106], and snapping shrimp [107], or invasive species [108,109]) and landscape [110], to name some examples from numerous papers published in the last ten years.…”
Section: Passive Acoustic Monitoring For Environmental Assessment Andmentioning
confidence: 99%
“…In the one study directly comparing PAM and aerial surveys, PAM was more reliable for detecting right whale presence in CCB, particularly at low whale densities (Clark, Brown, & Corkeron, ). Previous fixed‐location PAM studies have revealed the presence of right whales at times of year and/or places previously undocumented by recent visual observations (Bort, Parijs, Stevick, Summers, & Todd, ; Hodge, Muirhead, Morano, Clark, & Rice, ; Mellinger, Nieukirk, et al, ; Morano et al, ; Muirhead et al, ; Mussoline et al, ; Salisbury, Clark, & Rice, ; Whitt, Dudzinski, & LalibertĂ©, ). These studies, most of which were limited to 1 or 2 years, have demonstrated the value of PAM methods for filling in important gaps in our understanding of right whale occurrence patterns in space and time.…”
Section: Introductionmentioning
confidence: 95%